The Effect of Taxpayer Awareness and Income Level on The Compliance of Land Taxpayers of Rural and Urban Buildings in Margosari Village, Kulon Progo Regency, Yogyakarta - Evanny Emanuela Rumui; Rochmad Bayu Utomo (Publikasi Indonesia, 2024)
This study aimed to test whether taxpayer awareness and income level affect land and building tax in Margosari village, Kulon Progro district, Yogyakarta. This type of research is quantitative, with the research object being rural and urban building taxpayers in Margosari Village, Kulon Progo District, Yogyakarta. The population in this study were all land and building taxpayers in Margosari village, Kulon Progo Regency, Yogyakarta. The sample collection technique taken by the researcher uses a non-probability sampling technique with a purposive sampling method, namely one of the sampling intentionally with specific considerations from the researcher. Samples in this study were selected based on criteria, namely samples with land and building rights. The results of this study indicate that taxpayer awareness and income level significantly and positively affect taxpayer compliance in Margosari Village, Kulon Progo Regency, Yogyakarta.